2019
DOI: 10.1155/2019/8698746
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Iron Oxide on the Protective Photochromism of African Padauk

Abstract: African padauk is a tree whose wood is an excellent material for producing decorative items. The wood is susceptible to sunlight exposure and degrades severely, even after short exposures, which leads to discoloration. Ultraviolet irradiation is the main factor that produces discoloration. In this study, chemical changes occurring on the wood surfaces were analyzed by Fourier transform infrared spectroscopy. The discoloration of the African padauk was mainly because of the photodegradation of lignin and extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Padauk wood is used for making furniture, musical instruments, and for construction purposes. Although many applications are implemented, it is still possible to obtain many new applications of this material [ 22 , 23 ]. Thermal treatment of iroko and padauk wood caused a decrease in its density, colour darkening, and considerable improvement of dimensional stability [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Padauk wood is used for making furniture, musical instruments, and for construction purposes. Although many applications are implemented, it is still possible to obtain many new applications of this material [ 22 , 23 ]. Thermal treatment of iroko and padauk wood caused a decrease in its density, colour darkening, and considerable improvement of dimensional stability [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Wood is susceptible to degradation from UV light, resulting in discoloration. Wang et al [19] found that different concentrations of red iron oxide coatings have a strong inhibitory effect on the discoloration of African mahogany. Cirule et al [20] studied the addition of organic light stabilizers (UVA and HALS) and lignin stabilizers (HALS) to coatings to pretreat wood.…”
Section: Introductionmentioning
confidence: 99%